(untitled) (Research, Society and Development, 2022)
The objective of this study is to bring a set of research that identifies the possibilities of success that digital marketing can have on social media platforms, as a tool for publicity in public bodies, in the sense of giving greater transparency and publicity to its actions, and consequently, collaborate for a more effective and efficient public management. The studies chosen for the analyzes were selected based on a thorough search linked to journals and electronic databases of the Digital Library of Journals, Scielo (Scientific Electronic Library Online) and Google Academic, considering the following aspects: having a complete text in Portuguese, being published between the years 2017 to 2022, with the keywords social networks, digital marketing and public sector, selecting 20 articles that responded to the objective of this study. As a result of this bibliographical survey, digital marketing through social media platforms as a tool to influence public bodies was identified as one of the strategies already widely used in the dissemination of information to citizens, but due to social dynamics, its activities could be intensified. actions to obtain more expressive results in meeting the goals of public bodies to provide transparency and publicity to their actions, and with that, continuous improvements in the management of organizational communication and citizen involvement.